Peran Human Capital Business Partner & General Service PT Angkasa Pura 1 Kantor Cabang Adi Soemarmo Terhadap Efektivitas Kinerja Perusahaan - Intan Nurrohmah, Rahmadini; Retno Cahyani, Rusnandari (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2023)
The purpose of this article is to explain that human capital does not only reflect as "skills" derived from mental and physical abilities but the collective ability of the company to be able to produce the best solution based on the knowledge possessed by the people in the company, thus becoming one of the main components of intellectual capital (intangible assets) owned by the company. HR is capital that can continue to grow over time and the dynamics of the business environment. Human Capital Business Partner & General Services PT Angkasa Pura 1 Adi Soemarmo Branch Office has 2 main positions in supporting efforts to optimize employee productivity and increase customer satisfaction. The task is to justify the implementation of Human Capital Business Partner policies and strategies as a strategic partner in the field of human capital and management of industrial universal service activities and efficient office administration to support efforts to optimize employee productivity and increase customer satisfaction sourced from work plans and Industrial budgets (RKAP) and discipline in accordance with statutory regulations.